Rough weather [large type] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Spenser novel., 2008)
Parker once again proves he is a force of nature in this mystery where a hurricane hinders a kidnapping and Spenser goes on a search for the man responsible--the infamous Gray Man, who has both helped and hunted Spenser in the past.